2016
DOI: 10.1021/jacs.6b00893
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Molecular Structure of the Air/Water Interface from Quantum Simulations of the Sum-Frequency Generation Spectrum

Abstract: The molecular characterization of the air/water interface is a key step in understanding fundamental multiphase phenomena ranging from heterogeneous chemical processes in the atmosphere to the hydration of biomolecules. The apparent simplicity of the air/water interface, however, masks an underlying complexity associated with the dynamic nature of the water hydrogen-bond network that has so far hindered an unambiguous characterization of its microscopic properties. Here, we demonstrate that the application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
278
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(297 citation statements)
references
References 68 publications
(178 reference statements)
17
278
2
Order By: Relevance
“…17 In 2015, two new heterodyne-detected experiments with a more careful consideration of the reference used to determine the phase were performed by Yamaguchi, and Tahara and co-workers, which showed, in fact, that for neat H 2 O the low-frequency positive feature was absent 19,20 21 which does essentially confirm the result that there is no positive feature at low frequencies. We note that Nagata and co-workers have recently calculated sum-frequency spectra with ab initio MD simulations, 22 and Medders and Paesani have done the same 23 using their MB-pol model, 24 and the results of both groups are in good agreement with these new experiments.…”
supporting
confidence: 65%
“…17 In 2015, two new heterodyne-detected experiments with a more careful consideration of the reference used to determine the phase were performed by Yamaguchi, and Tahara and co-workers, which showed, in fact, that for neat H 2 O the low-frequency positive feature was absent 19,20 21 which does essentially confirm the result that there is no positive feature at low frequencies. We note that Nagata and co-workers have recently calculated sum-frequency spectra with ab initio MD simulations, 22 and Medders and Paesani have done the same 23 using their MB-pol model, 24 and the results of both groups are in good agreement with these new experiments.…”
supporting
confidence: 65%
“…61,62 Although it was shown that many-body effects can be decomposed, at least to some extent, into effective pairwise contributions using force-matching, 88 more recent studies have demonstrated that the explicit account of 3B effects is essential for a physically correct description of heterogeneous environments such as the air/water interface. 89,90 …”
Section: Many-body Analytical Potential Energy Functionsmentioning
confidence: 99%
“…Although the E3B models represent an improvement over common pairwise additive force fields, a recent analysis of the heterodyne-detected vibrational sum-frequency generation (HD-vSFG) spectrum of the air/water interface in terms of many-body contributions suggests that, due to the empirical parametrization, 3B effects are possibly overemphasized in the E3B models. 90 …”
Section: Many-body Analytical Potential Energy Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,[31][32][33][34] While the conventional SFG measurement detects the square of the second-order nonlinear susceptibility | χ (2) | 2 (hereafter χ (2) is denoted as χ), phase-sensitive 35 or heterodyne-detected 36 vibrational SFG (HD-VSFG) measurement can detect the phase of χ (or the imaginary part of χ, Im[ χ]) besides its amplitude, which enables us to detect the orientation of water molecules at the interface, proton-up or proton-down (H-up or H-down). 37 Several HD-VSFG studies clarified detailed molecular orientation at air/water [38][39][40][41][42][43][44][45][46] and lipid (or surfactant)/water [47][48][49][50][51] interfaces.…”
Section: Introductionmentioning
confidence: 99%